Frequency of endophthalmitis following intravitreal bevacizumab injection using povidone-iodine vs povidone-iodine with topical antibiotics as prophylaxis in patients of macular oedema - Jamil, Muhammad Itban; Ahmed, Najam Iqbal; Javed, Maham; Ashraf, Bushra; Bint Amjad, Roshaan; Akhtar, Sana (Biological and Clinical Sciences Research Journal, 2025)
This study compared povidone-iodine alone versus povidone-iodine with antibiotics to prevent endophthalmitis after intravitreal bevacizumab injections for macular oedema. It aimed to find the best infection prevention method. Objective: To determine the efficacy of per-operative 5% povidone-iodine alone vs combined per-operative 5% povidone-iodine with topical antibiotics for reducing the frequency of endophthalmitis in patients undergoing repeated intravitreal injection of Anti-VEGF (Bevacizumab). Methods: This randomised control trial was conducted at the Department of Ophthalmology, Sir Ganga Ram Hospital, Lahore. Patients meeting inclusion criteria were enrolled after taking informed written consents, and two equal groups were made on a random basis using a lottery method: Group A (Povidone Iodine Alone) and Group B (Povidone Iodine with Topical Antibiotics). The procedure was performed per the hospital’s standard protocol, and variables were noted for data analysis. Results: The mean age was 51.23±12.43 years, with a balanced gender ratio (52.6% male, 47.4% female). Injections were predominantly in the right eye (52.9%) versus the left (47.1%). Diabetic macular oedema (57.4%) was most prevalent, followed by choroidal neovascularization (17.1%), central retinal vein occlusion (8.9%), branch retinal vein occlusion (10.9%), and other pathologies (5.7%). Groups A and B had similar baseline characteristics (p>0.05). Both groups had a 0.6% endophthalmitis rate (p=1.000), each with 175 patients. Conclusion: This study comparing 5% povidone-iodine alone versus 5% povidone-iodine with topical antibiotics for prophylaxis during intravitreal bevacizumab injections did not demonstrate a significant difference in the incidence of endophthalmitis between the two groups.